TEACHERS’ BASIC QUESTIONINGS USED BY ENGLISH TEACHERS IN TEACHING ENGLISH (English Education Journal, 2015)
This study examined the use of teachers’ basic questionings of Sydney Micro Skill (1983) in Teaching English as a Foreign Language (TEFL). There were nine components of teachers’ basic questionings, namely structuring, focusing, phrasing, redirecting, distributing, reacting, pausing, prompting, and changing the level of cognitive demand. The objectives of this study were to describe the types of basic questionings, explain the teachers’ ways in keeping the students active to respond their questions and explain why the teachers use those teachers’ basic questionings. It was a qualitative research which was also supported by quantitative data. It used audio visual, observation/field note and interview to collect data. The result showed that most of English teachers applied those nine components to build a good classroom interaction and the dominant was distributing. The teachers had four ways in keeping the students active to respond their questions; they used questions randomly, interesting medium while delivering the questions, active in motivating the students, and promoted a group discussion. Moreover, the teachers also had reasons why they used those teachers’ basic questionings, such as to find out the students’ attitudes, determine the students’ understanding, and to motivate and appreciate the students.